Software de simulación @risk para cuantificar y valorar riesgos de proyectos - Abata Aguilar, Elsa María (2015)
This research work was developed in order to create a user guide and a case of @ RISK simulation software using Monte Carlo method. It considers its importance in the business world. Nationally most firms do not have tools that allow risk analysis modeling perform at various venues within the same financial areas to help decision making. Research methodologies were used such as surveys. They were applied with Engineering School students and Commercial specialist teachers in administrative subject at Technical University of Cotopaxi. Bibliographic and documentary research has allowed different approaches and theories of several authors to support investigation which was also applied. In addition, information directly obtained through observation, which it allowed to determine the current problems. It concludes that people do not have extensive knowledge about new technologies day by day. They are changing in the social environment.